2008
DOI: 10.1158/1055-9965.epi-07-2890
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene Diol Epoxide-Induced Chromosome 9p21 Aberrations Are Associated with Increased Risk of Bladder Cancer

Abstract: Purpose: Loss of chromosome 9p21 is one of the most frequent genomic alterations in bladder cancer. Alterations of 9p21 and p16 are also frequently seen in the epithelial cells of chronic smokers. We hypothesize that 9p21 is a molecular target of benzo(a)pyrene diol epoxide (BPDE), the metabolic product of tobacco carcinogen benzo(a)pyrene, and 9p21 BPDE sensitivity is a genetic susceptibility factor for bladder cancer. Material and Methods: In this case-control study of 203 bladder cancer cases and 198 matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…CYP1A1 is well known for its role in the bioactivation of carcinogens such as aromatic amines and polycyclic aromatic hydrocarbons (PAHs) [21], [22]. Induction and a high activity of the CYP1A1 have been associated with increased toxicity and cancer risk [23], [24]. CYP2B6 is also expressed in the brain, highly expressed in specific cells such as cortical pyramidal cells and astrocytes [25] and may be an important factor in the metabolism of drugs acting on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…CYP1A1 is well known for its role in the bioactivation of carcinogens such as aromatic amines and polycyclic aromatic hydrocarbons (PAHs) [21], [22]. Induction and a high activity of the CYP1A1 have been associated with increased toxicity and cancer risk [23], [24]. CYP2B6 is also expressed in the brain, highly expressed in specific cells such as cortical pyramidal cells and astrocytes [25] and may be an important factor in the metabolism of drugs acting on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prevalence of different Ahr alleles, which might result in the formation of proteins with different ligand affinities [41] can be excluded. (ii) Both the mRNA expression levels of both genes and the corresponding intestinal protein concentrations were unchanged in TLR2 −/− animals compared to WT mice (Table 2, Figure 2) (iii) CYP1A2, which also depends on AHR/ARNT regulation [10], is expressed at high levels in the liver and also moderately in the intestine. This would not be the case if the AHR functionality would be impaired; (iv) CYP1A1 is induced in the liver of TLR2 −/− mice after exposure to BaP, indicating a well-functioning regulation by AHR/ARNT in this organ; (v) none of the genes that were shown to be altered by genetic deletion of AHR in mice [42] were found to be significantly changed in the TLR2 −/− mice (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Data from epidemiological studies, biochemical and molecular investigations support the idea of PAH such as BaP to be primary causative carcinogens in the lung [9] and the bladder [10]. The key reactive intermediate benzo(a)pyrene-7,8-diol-9,10-epoxide (BPDE) can link covalently to DNA, therefore causing genetic aberrations [10]. BPDE is formed endogenously in a multi-step procedure in which cytochrome P450 (CYP) subclasses CYP1A1 and CYP1B1 are of special relevance in both metabolic activation (epoxidation) and detoxication [9].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…DNA damage/repair capacity can be quantified by phenotypic assays such as the mutagen sensitivity assay, which quantifies chromatid breaks induced by mutagens in short-term cultures of peripheral blood lymphocytes (PBLs) (8). Numerous studies have shown that individuals with higher mutagen sensitivity phenotype are at increased risk of various cancers (9–12). DNA double-strand breaks (DSBs) is one of the major forms of DNA damage.…”
Section: Introductionmentioning
confidence: 99%